2018
DOI: 10.1007/s00590-018-2174-2
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with plate fixation of acute midshaft clavicle fractures versus non-unions

Abstract: An important consideration when counselling patients with midshaft clavicle fractures is whether operative treatment of non-union, if it develops after non-operative treatment, is associated with higher complication rate than acute fracture fixation. The aim of this study is to compare complications and re-operations after open reduction and plate fixation for acute midshaft clavicle fractures versus non-unions. The study was retrospective. There were 90 patients in the acute fixation group and 20 patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…17 In our study, the complication rate was 20%, being similar to other studies. [18][19][20][21] In a meta-analysis conducted by Wang et al, 17 the frequency of postoperative complications was similar in both forms of fixation. Based on our results, the group fixed with plate presented the highest number of complications (n = 9), but without significant and 14.4 mm for nail.…”
Section: Discussionmentioning
confidence: 91%
“…17 In our study, the complication rate was 20%, being similar to other studies. [18][19][20][21] In a meta-analysis conducted by Wang et al, 17 the frequency of postoperative complications was similar in both forms of fixation. Based on our results, the group fixed with plate presented the highest number of complications (n = 9), but without significant and 14.4 mm for nail.…”
Section: Discussionmentioning
confidence: 91%
“…A single-center study from the United Kingdom including 20 patients with nonunion found similar results, with more complications compared with acute surgery and a tendency toward more frequent reoperations. 10 By use of logistic regression, however, these findings were not significant, potentially because of the limited number of patients included.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, data comparing acute surgery and surgery for nonunion are scarce, and the results are conflicting. 5,8,10 Our study had 2 main objectives: First, we wanted to evaluate our step-wise treatment protocol for patients with clavicle fractures to determine our success rate of conservative treatment. Second, we evaluated the incidence of complications after clavicle plate fixation in patients undergoing acute surgery vs. delayed surgery, with specific attention regarding patients with postoperative AC joint dislocation.…”
mentioning
confidence: 99%
“…There is increasing evidence that delayed primary fixation in the first three months post-injury is a valid alternative without an apparent increase in complications [47][48][49] . Delayed recovery following non-operative management may predict union and can be accurately judged on a patient reported QuickDASH score and other objective clinical features at six weeks post-injury [ 50 , 51 ].…”
Section: Claviclementioning
confidence: 99%